Natural killer cells are scarce in colorectal carcinoma tissue despite high levels of chemokines and cytokines - Halama, Niels; Braun, Monika; Kahlert, Christoph; Spille, Anna; Quack, Christian; Rahbari, Nuh Nabi; Koch, Moritz; Weitz, Jürgen; Kloor, Matthias; Zörnig, Inka; Schirmacher, Peter; Brand, Karsten; et al. (Clinical cancer research, 2011)
Purpose: Tumor infiltrating T lymphocytes in colorectal cancer (CRC) have prognostic impact, but the role of natural killer (NK) cells in CRC tissue is unclear. The contribution of intratumoral cytokines and chemokines in shaping the composition of the inflammatory lymphocytic infiltrate is also unclear.Experimental Design: In this study, localization and densities of NK and T cells within primary CRC, CRC liver metastases, adenomas, and normal tissues were analyzed on whole tissue sections from 112 patients. In a subset of these patients, the most important 50 cytokines and chemokines were quantified in paired serum, primary CRC and adjacent mucosa samples and in CRC liver metastases and correlated with NK and T-cell infiltration, respectively.Results: The various compartments displayed characteristic differences like significantly higher chemokine concentrations in CRC tissue. Most importantly, despite high local chemokine levels, NK cells were generally scarce within CRC tumor tissues, independent of human leukocyte antigen (HLA) class I expression. Adjacent normal mucosa contained normal levels of NK cells. In contrast, corresponding T-cell numbers varied substantially and were positively correlated with higher chemokine levels.Conclusions: Our findings indicate a distinct regulation of NK cells versus T cells in the CRC tumor microenvironment. NK-cell migration into CRC tumor tissue is obviously impaired early during tumor development by mechanisms that do not affect T-cell infiltration. Clin Cancer Res; 17(4); 678-89. ©2011 AACR.
Gesehen am 29.07.2022